2019
DOI: 10.1128/aac.01679-19
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem-Tobramycin Combination Regimens Combat Carbapenem-Resistant Pseudomonas aeruginosa in the Hollow-Fiber Infection Model Simulating Augmented Renal Clearance in Critically Ill Patients

Abstract: Augmented renal clearance (ARC) is common in critically ill patients and is associated with subtherapeutic concentrations of renally eliminated antibiotics. We investigated the impact of ARC on bacterial killing and resistance amplification for meropenem and tobramycin regimens in monotherapy and combination. Two carbapenem-resistant Pseudomonas aeruginosa isolates were studied in static-concentration time-kill studies. One isolate was examined comprehensively in a 7-day hollow-fiber infection model (HFIM). Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 77 publications
3
20
0
Order By: Relevance
“…Thus, the question on PTZ-aminoglycoside combination vs PTZ/meropenem monotherapy on clinical outcome remained unanswered in this study. However, in agreement with previous in vitro studies (51,52,139) on benefits of combination therapy, a clinical study reported that beta-lactam and aminoglycoside combination therapy reduced mortality in patients with sepsis caused by carbapenemase-producing Enterobacterales (328). Also, a meta-analysis reported that combination therapy in patients with septic shock improves the survival of patients > 25% (147).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Thus, the question on PTZ-aminoglycoside combination vs PTZ/meropenem monotherapy on clinical outcome remained unanswered in this study. However, in agreement with previous in vitro studies (51,52,139) on benefits of combination therapy, a clinical study reported that beta-lactam and aminoglycoside combination therapy reduced mortality in patients with sepsis caused by carbapenemase-producing Enterobacterales (328). Also, a meta-analysis reported that combination therapy in patients with septic shock improves the survival of patients > 25% (147).…”
Section: Discussionsupporting
confidence: 81%
“…Few studies have investigated the effect of combination therapy against Enterobacterales, with most studies investigating the effect of combination antibiotics against P. aeruginosa (51,52,139). In this context, differences in cell wall thickness, presence of efflux pumps and the presence of different beta-lactamases are likely key differences between these bacterial species that mediate beta-lactam resistance, which may explain the improved bacterial killing with clinically relevant doses of PTZ used in our study compared with others conducted using P. aeruginosa (321,322).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Treatment failure with meropenem monotherapy against P. aeruginosa in previous HFIM studies simulating ARC was observed despite fT >MIC exceeding 40%. 9,11 In the first of those studies, meropenem dosing regimens (2, 1 and 0.5 g q8h as short-term infusions) failed to yield sustained bacterial killing and resistance suppression for a susceptible P. aeruginosa isolate (MIC of 0.25 mg/L). 9 In the second study evaluating a carbapenem-resistant P. aeruginosa isolate (MIC of 8 mg/L), in addition to short-term infusion regimens, meropenem at 3 or 6 g/ day CI produced ~ 3-log killing by 7 hours followed by extensive regrowth similar to the control arm.…”
Section: Discussionmentioning
confidence: 99%
“…7 In the dynamic hollow-fiber infection model (HFIM) simulating pharmacokinetic (PK) profiles typical of patients with ARC, approved doses of meropenem and piperacillin as monotherapy against a susceptible P. aeruginosa isolate failed to achieve sufficient bacterial killing and resistance suppression. 8,9 Beta-lactam and aminoglycoside combinations studied in the HFIM under ARC conditions demonstrated good bacterial killing and resistance suppression, 10,11 but this combination has the potential to cause aminoglycoside-associated nephrotoxicity. 12 Beta-lactam and quinolone combinations have been found to produce substantial bacterial killing and resistance suppression of P. aeruginosa; 13,14 however, these combinations have never been evaluated in the HFIM under conditions of ARC.…”
Section: How Might This Change Clinical Pharma-cology or Translationamentioning
confidence: 99%